Development of legislative framework for the protection of women victims of violence in Serbia - Ćopić Sanja (Temida, 2019)
The aim of the paper is to provide an overview of advocacy of the civil society in Serbia for legal reforms for better protection of women from violence and the development of the legislative framework for the protection of women victims of violence. Advocacy for legal protection of women against violence in Serbia began already in 1980s, primarily due to the activities of women’s groups and feminist researchers. Advocacy activities intensified during the 1990s. In 1994, the Group for Women’s Rights of the European Movement in Serbia prepared a first draft of amendments to the laws related to domestic violence and marital rape. Although not successful, this advocacy was very important in terms of raising awareness of state officials and general public about violence against women. First legal reforms and establishment of normative framework for the protection of women against violence, especially domestic violence, sexual violence and human trafficking, occurred only after political changes in 2000. They were initiated and largely based on drafts written by the experts of the Victimology Society of Serbia. The basis for these changes was the proposal of a harmonized reform of several laws in order to ensure criminal, civil and misdemeanour protection of women against various forms of gender- based violence developed in 1998 and further improved after 2000. Advocacy that followed resulted in first instruments of legal protection of women victims of violence: domestic violence was foreseen as a standalone criminal offense, restraining orders have been introduced, legal protection against sexual violence has been improved, and human trafficking was criminalized. Since the acceptance of Serbia’s EU candidacy and the start of the EU integration process, a strategic framework for the protection of women against violence has been developed; the protocols for dealing with domestic and intimate partner violence and other implementation instruments have been adopted, which set up a basis for more efficient implementation of legal norms in practice. Ratification of the Council of Europe Convention on preventing and combating violence against women and domestic violence and opening negotiations for the EU accession set a new framework for advocacy and contributed to further improvement of legal protection of women against violence. Stalking, sexual harassment, female genital mutilation and forced marriage have been incriminated. The Law on the Prevention of Domestic Violence was adopted, which aims to ensure effective prevention from domestic violence and urgent, adequate and effective protection and support to victims through improvement of coordination and cooperation between competent services. This should ensure integrated, multi-sector and human rights-based approach to prevention, prosecution and protection of women victims of violence. Normative framework for the protection of women against violence is to a large extent in compliance with relevant international standards and the European law. However, it still needs to be fully harmonized with the Istanbul Convention and other ratified international treaties. On the other hand, it remains to monitor application of legislation in practice in order to assess its consistency, effectiveness and continue evidence-based advocacy for further improvement of protection of women victims of violence. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 179044]